Impaired lung mitochondrial respiration following perinatal nicotine exposure in rats - Cannon, Daniel T. (Lung, 2016)
Perinatal smoke/nicotine exposure predisposes to chronic lung disease and morbidity. Mitochondrial abnormalities may contribute as the PPARγ pathway is involved in structural and functional airway deficits after perinatal nicotine exposure. We hypothesized perinatal nicotine exposure results in lung mitochondrial dysfunction that can be rescued by rosiglitazone (RGZ; PPARγ receptor agonist). Sprague-Dawley dams received placebo (CON), nicotine (NIC, 1 mg.kg(−1)), or NIC+RGZ (3 mg.kg(−1)) daily from embryonic day 6 to postnatal day 21. Parenchymal lung (~10mg) was taken from adult male offspring for mitochondrial assessment in situ. ADP-stimulated O(2) consumption was less in NIC and NIC+RGZ compared to CON (F[2,14]=17.8; 4.5±0.8 and 4.1±1.4 vs. 8.8±2.5 pmol.s.mg(−1); p<0.05). The respiratory control ratio for ADP, an index of mitochondrial coupling, was reduced in NIC and remediated in NIC+RGZ (F[2,14]=3.8; p<0.05). Reduced mitochondrial oxidative capacity and abnormal coupling was evident after perinatal nicotine exposure. Rosiglitazone improved mitochondrial function through tighter coupling of oxidative phosphorylation.